2017
DOI: 10.1016/j.jtumed.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with anxiety and depression among type 2 diabetes in Qassim: A descriptive cross-sectional study

Abstract: Objectives To assess the prevalence of anxiety and depression and to identify their associated risk factors among people with type 2 diabetes mellitus. Methods A cross-sectional, single-centre study that included 300 adults with type 2 diabetes mellitus was conducted at The Diabetic Center of King Saud Hospital in the Qassim region. Anxiety and depression were measured by using the Hospital Anxiety and Depression Scale (HADS). Multivariable analysis using multiple logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 31 publications
7
23
3
1
Order By: Relevance
“…Similar to two studies of Saudi patients with diabetes that examined anxiety in comparison to other mental health problems, anxiety was the most common form of psychological distress [25, 26]. The prevalence of anxiety in our sample is similar to that found among T2DM patients in the central region of Saudi Arabia (43.6%) but higher than the prevalence reported among patients in the northern parts of Saudi Arabia (28.5%) [25, 26].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to two studies of Saudi patients with diabetes that examined anxiety in comparison to other mental health problems, anxiety was the most common form of psychological distress [25, 26]. The prevalence of anxiety in our sample is similar to that found among T2DM patients in the central region of Saudi Arabia (43.6%) but higher than the prevalence reported among patients in the northern parts of Saudi Arabia (28.5%) [25, 26].…”
Section: Discussionsupporting
confidence: 86%
“…This number was used to calculate the sample size needed for this study. Considering a 95% confidence interval (CI), a 5% margin of error, and a presumed prevalence of depression of 50% (based on data from the Alqassem region) [26], the minimum required sample size was calculated to be 375. Considering a 10% non-response rate, the final sample size was 450.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other published studies, our finding is almost similar to the study in Pakistan which revealed 49.2% depression in patients with DM [ 8 ]. However, prevalence of depression is higher in our sample than that in the studies conducted in Jordan [ 25 ], South London King's College hospital [ 26 ], Palestine [ 27 ], Saudi Arabia [ 28 ], and North-Eastcoast Malaysia [ 29 ]. Similarly, a meta-analysis of 42 published studies held in the United States reported the prevalence of major depression among 11% of diabetic patients and the prevalence of clinically serious depression in 31% of patients [ 30 ].…”
Section: Discussioncontrasting
confidence: 72%
“…A recent cross-sectional study also demonstrated the cognitive effect of T2DM. The study concluded that there is a significant association between depression, anxiety, and T2DM [27].A study examines the relationship between the health-related quality of life and physical activity in T2DM. They found a negative correlation between the quality of life and the level of physical activity.…”
Section: Discussionmentioning
confidence: 99%